TUNABLE SURFACE PLASMON RESONANCES OF Au@TiO2 CORE-SHELL NANOPARTICLES ON THE DSSC (DYE SENSITIZED SOLAR CELLS) PERFORMANCE - Friska Ayu Fitrianti Sugiono; Doty Dewi Risanti (Jurnal Sains Materi Indonesia, 2019)
Plasmonic core-shell nanoparticles, i.e. gold can improve the efficiency of Dye-sensitized Solar Cell by increase the light harvesting due to the strong near-field effect LSPR (Localized Surface Plasmon Resonance). To achieve maximum enhancement, the morphology of core-shell need to be optimized with coated either by insulator such as semiconductor, i.e. TiO2. In this paper, morphology of Au@TiO2 core-shell precisely control by various TiO2 volume and systematically study its influence on the plasmonic enhancement effect. A gold solution was prepared using Turkevich method. The crystal structure of the powders was determined by powder X-ray diffraction (XRD). The optical properties were measured by UV-Vis absorption spectroscopy using UV-Vis Lambda 750. The photocurrent action spectra or IPCE in visible light spectrum was obtained by adjusting wavelength of incident light, i.e. series connection of halogen lamp and monochromator. UV-Vis absorption spectra of core–shell showed the position of the surface plasmon Au band in the range of 500–550 nm. According to UV-Vis characterization, all samples studied show weak surface plasmon resonance response (~520 to 550 nm) as indicative of the thick TiO2 shells for individual core-shell Au@TiO2.Tunable Surface Plasmon Resonances of Au@TiO2 Core-shell Nanoparticles on the DSSC (Dye Sensitized Solar Cells) Performance